Health Impacts of Pesticide Use and Associated Safety Practices among Farmers in A Rural Place in Palpa District of Nepal - Lamsal, Suresh; Poudel, Kamal; Sharma, Roshani; Poudel, Jamuna; Khanal, Asmita; Sharma, Vidya (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: The unsafe and indiscriminate use of pesticide in agriculture represents a major human health problem. The aim of this study was to assess the level of safety practices regarding pesticides use and its effect on health among farmers of Rampur municipality. Method: The research was a descriptive cross-sectional study in the rural area of the Lumbini Province and purposive sampling was used to collect data. The study assessed pesticide safety practices and health effects among 227 farmers in Rampur Municipality, Palpa. Result: While all farmers recognized pesticides as harmful, 79.29% used them in crops, and 96.5% had no formal training. Unsafe practices were common, including storing pesticides in living areas (26.11%) and improper disposal methods. Pesticide exposure occurred mainly via the oral route (48.5%), with 14.5% unaware of the entry route. Only 31.11% bathed fully after pesticide use. Despite high awareness, safety practices were poor. Conclusion: The study recommends safety training, stricter law enforcement, and promotion of integrated and non-synthetic pest control methods. Strengthening farmers’ access to protective equipment and ensuring routine monitoring and follow-up will further support safer pesticide handling and reduce long-term health risks.